2021
DOI: 10.1029/2020gl092095
|View full text |Cite
|
Sign up to set email alerts
|

Dust Storm‐Enhanced Gravity Wave Activity in the Martian Thermosphere Observed by MAVEN and Implication for Atmospheric Escape

Abstract: Lower atmospheric global dust storms affect the small‐ and large‐scale weather and variability of the whole Martian atmosphere. Analysis of the CO2 density data from the Neutral Gas and Ion Mass Spectrometer instrument on board NASA's Mars Atmosphere Volatile EvolutioN (MAVEN) spacecraft show a remarkable increase of gravity wave (GW)‐induced density fluctuations in the thermosphere during the 2018 major dust storm with distinct latitude and local time variability. The mean thermospheric GW activity increases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 46 publications
3
53
0
Order By: Relevance
“…It shows that the mean amplitude of GW‐induced temperature fluctuations (false|Tfalse|, Figure 7a) grows with height reaching up to 10 K near the top of the domain. At higher altitudes (170–220 km), the in situ measurements with Neutral Gas and Ion Mass Spectrometer (NGIMS) on board MAVEN revealed even larger GW magnitudes over the same time (Leelavathi et al., 2020; Yiğit et al., 2021). The latitudinal structure of the GW activity in the mesosphere and lower thermosphere is not uniform.…”
Section: Resultsmentioning
confidence: 99%
“…It shows that the mean amplitude of GW‐induced temperature fluctuations (false|Tfalse|, Figure 7a) grows with height reaching up to 10 K near the top of the domain. At higher altitudes (170–220 km), the in situ measurements with Neutral Gas and Ion Mass Spectrometer (NGIMS) on board MAVEN revealed even larger GW magnitudes over the same time (Leelavathi et al., 2020; Yiğit et al., 2021). The latitudinal structure of the GW activity in the mesosphere and lower thermosphere is not uniform.…”
Section: Resultsmentioning
confidence: 99%
“…higher altitude, a type of seasonal variability observed by Liu et al (2019) and reported in 34P by Elrod et al (2019). In addition, Leelavathi et al (2020) and Yiğit et al (2020) recently showed that upper atmospheric GW amplitudes increased by a factor of 2 or more during 34P, despite the high likelihood that GWs would be more strongly filtered by convective instability in the warmer conditions near 100 km that prevailed during 34P (England et al 2017;Vals et al 2019;Leelavathi et al 2020;Yiğit et al 2020).…”
Section: Introductionmentioning
confidence: 85%
“…As noted by Slipski et al (2018), an atmosphere with a higher homopause, i.e., one in which atmospheric gases are well mixed to higher altitude, is one in which escaping species are less isotopically fractionated. In addition, GWs in the upper atmosphere strongly affect exospheric temperatures locally and possibly enhance atmospheric escape (Parish et al 2009;Walterscheid et al 2013;England et al 2017;Williamson et al 2019;Leelavathi et al 2020;Yiğit et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Gravity waves (GWs) are omnipresent in the atmosphere of Mars and continuously disturb it at all heights. Recent observations not only provided ample evidence for their existence, but also determined their seasonal and spatial climatology in the lower (Heavens et al., 2020) and upper atmosphere (Jesch et al., 2019; Leelavathi et al., 2020; Li et al., 2021; Nakagawa et al., 2020; Siddle et al., 2019; Starichenko et al., 2021; Vals et al., 2019; Yiğit, Medvedev, Benna, et al., 2021; Yiğit, Medvedev, & Hartogh, 2021). The main dynamical role of GWs in planetary atmospheres is to re‐distribute momentum and energy between atmospheric layers, thus providing a vertical coupling between the lower and the upper atmosphere (Yiğit & Medvedev, 2015, 2019).…”
Section: Introductionmentioning
confidence: 99%